Three new Eastern-Mediterranean endemic species of the Merodon aureus group (Diptera: Syrphidae) - Veselić, Sanja; Vujić, Ante; Radenković, Snežana (Zootaxa, 2017)
The Merodon aureus group (Diptera: Syrphidae: Eristalinae) comprises a number of different subgroups and species complexes, including the M. bessarabicus subgroup, which is revised here. In this study, we present an identification key to species complexes and species within the M. bessarabicus subgroup and focus on clarifying the taxonomic status of previously described species within this subgroup, based on a study of the type material. Merodon flavicornis Macquart, a species with an unknown type locality, is re-evaluated and recognized as a valid Western Mediterranean species from France. We describe a new species, M. adriaticus sp. n., from M. bessarabicus subgroup, as well as another two species with a clearly separate position within the M. aureus group due to their distinct morphological features: M. nisi sp. n. and M. robustus sp. n.. Results of the present study indicate the high diversity and endemism levels of the genus Merodon in Europe.